Factors Associated with Reduced Function and Quality of Life among Adult People with HIV with Depression and Substance Use in the Asia-Pacific Region - Rajasuriar, Reena (Archīum Ateneo, 2023)
Background Depression and substance use (SU) disorders are prevalent among people with HIV (PWH) and impact health outcomes despite successful antiretroviral therapy (ART). We explored quality of life, functional ability and associated factors among PWH screened positive for depression and/or SU. Methods This cross-sectional study recruited adult PWH during routine follow-up at five HIV clinical sites in the Asia-Pacific region. Participants were screened for depression using Patient Health Questionnaire-9 and SU using Alcohol, Smoking, and Substance Involvement Screening Test (ASSIST). Quality of life (QoL) was assessed with WHOQOL-HIV BREF and functional ability with World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0). Factors associated with mean QoL and disability scores were analysed using linear regression. Results Of 864 PWH enrolled, 753 screened positive for depression or SU. The median (interquartile range, IQR) age was 38 (31-47) years and 97% were on ART. Overall mean WHOQOL-HIV BREF and WHODAS scores indicated greater impairment with increasing depressive symptom severity and SU risk. In multivariate analysis, PWH reporting previous trauma/stress (difference = 2.7, 95% confidence interval [CI] 1.5-3.9, P < 0.001) and past mental health diagnosis (difference = 5.0, 95% CI 2.9-7.1, P < 0.001) were associated with greater disability and poorer QoL scores across multiple domains (P < 0.01 for all). Higher CD4 T-cell counts was also associated with better QoL scores and functional ability.Conclusion:PWH with depression/SU experienced poorer QoL and function despite routine engagement in HIV care. Efforts to integrate mental health services and interventions addressing disability into HIV management should be prioritized in the region.